2020
DOI: 10.17079/jkgn.2020.22.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Person-centered Dementia Care Education Program for Nursing Home Staff

Abstract: This study aimed to develop and evaluate the effects of a person-centered dementia care education program on Korean nursing home staff. Methods: The person-centered dementia care education program was developed and evaluated using cluster-randomized, single-blind, and controlled pretest-posttest design. A total of 62 nursing home staff (31 in the experimental group and 31 in the control group) from four nursing homes participated in this study. The experimental group received the person-centered dementia care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Therefore, improving evidence-based knowledge related to restraint application is important for reducing the use of physical restraints. It is necessary to develop educational programs aimed at reducing the use of physical restraints based on previous studies that have shown an improvement in overall knowledge levels through systematic and ongoing education [ 14 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving evidence-based knowledge related to restraint application is important for reducing the use of physical restraints. It is necessary to develop educational programs aimed at reducing the use of physical restraints based on previous studies that have shown an improvement in overall knowledge levels through systematic and ongoing education [ 14 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, attitude toward agency, in particular, can have a significant impact on SDM as it reflects the care provider’s belief in the care receiver’s ability to make decisions regarding their own actions. A study implementing a person-centered dementia care education program, which included curriculum components focused on “valuing people” and “personal perspectives” for the staff at nursing homes, demonstrated improvements in person-centered attitude [ 37 ]. Notably, it is necessary to improve person-centered attitudes by providing person-centered care education through various approaches such as incorporating videos or images [ 37 ], ICT technologies such as touchscreen technology [ 38 ], and role-playing strategies [ 39 ], subsequently enhancing SDM practices.…”
Section: Discussionmentioning
confidence: 99%
“…A study implementing a personcentered dementia care education program, which included curriculum components focused on 'valuing people' and 'personal perspectives' for the staff at nursing homes, demonstrated improvements in person-centered attitude [29]. Notably, it is necessary to improve person-centered attitudes by providing person-centered care education through various approaches such as incorporating videos or images [29], ICT technologies such as touchscreen technology [30], and role-playing strategies [31], subsequently enhancing SDM practices.…”
Section: Discussionmentioning
confidence: 99%